Don't forget about the adjuncts! - Tomlin, Antione D. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"Don't Forget About the Adjuncts! is a work that creates space for adjuncts to share their experiences navigating workspaces within higher education and their experiences as part-time faculty. The primary goal of this book is to allow adjuncts to share their experiences navigating workspaces as frequently undervalues faculty in higher education. While frequently, adjunct faculty can feel unheard within higher education institutions, this book offers a platform for adjunct voices to be heard loud and clear. Contributing authors share the advantages and challenges they experience as adjuncts and the impact these experiences have on their well-being and career trajectory. Moreover, the authors provide insight and advice on how current and potential adjuncts can succeed and thrive, even with all the barriers or obstacles they face. The adjunct voices in this text have a wealth of knowledge and disciplines represented, expertise, and years of experience in higher education. Additionally, authors also come from all over the United States. With this range of expertise and knowledge, authors also provide advice, strategies, and ways of being for institutions to support their adjunct faculty and for adjuncts to support themselves. While many challenges are thrown at adjunct faculty, we are not suggesting that all adjunct faculty face the same issues. Moreover, this book serves as a space for contributing authors not to speak for all adjunct faculty but themselves. As editor and previous adjunct faculty myself, I encouraged and pushed all contributing authors to stand in their truth and take pride in this role. This book is the outcome of adjunct faculty loving and supporting their profession. Higher education institutions, colleagues, and other stakeholders can learn a great deal from the narratives and experiences shared to look at the intentional recruitment, retention, and psychological well-being of adjunct faculty. Thus, Don't Forget About the Adjuncts! is positioned to be a must-read for all higher education professionals, institutions, and stakeholders looking for strategies to do right by and for adjunct faculty"-- Provided by publisher.
Keywords: College teachers, Part-time -- United States.; Education -- Schools -- Levels -- Higher.; Teaching staff.; Higher education, tertiary education.; elektronické knihy; electronic books